Analysis Of The Influence Of System Quality, Perception Of Usability, And Perception Of Ease Of Use On User Satisfaction In BWS Mobile Banking With The Technology Acceptance Model (TAM) Approach - Mega Fajriyah (Jurnal Syntax Transformation, 2024)
Mobile banking is very effective in conducting non-cash transactions, especially during the pandemic, which requires no direct contact to make transactions. So, with the current phenomenon and reality, banks, in particular, are flocking to launch mobile banking applications, including BWS mobile banking. This study aims to analyze the effect of system quality, perceived usefulness, and perceived ease of use on BWS Mobile Banking user satisfaction with the Technology Acceptance Model (TAM) approach. The method in this study uses quantitative methods, with primary data sources (where the data collection technique uses a questionnaire method via Google form) which are distributed through the WhatsApp group and secondary data (data from the PT Bank Woori Saudara website and the Woori Global Standard System (WGSS) database). Research data analysis using the Statistical Product and Service Solutions (SPSS) version 26.0 program. The results of this study can determine that the variables of System Quality, Perceived Usefulness, and Perceived Ease of Use have a positive effect on User Satisfaction. The results of the user satisfaction test show that the Perceived usefulness variable Because high Perceived usefulness tends to provide a positive experience to users; they will feel that using the application provides significant value or benefits because satisfaction can be influenced by the extent to which the application effectively meets user needs or goals. The test result of the lowest user satisfaction level is the system quality variable, where PT Bank Woori Saudara must improve system quality and user satisfaction because system quality must have a fast response time, be reliable, flexible, and have good security.